Tinjaun Kritis Terhadap khotbah Jonathan Edwards: Sinners in the Hands of an Angry God - Timotius Timotius; Sutrisno Sutrisno (JURNAL LUXNOS, 2022)
Abstract: Jonathan Edwards' sermon, with the theme Sinners in the Hands of an Angry God, received a negative response from scholars. They said Edwards' sermon was sadistic and frightening because hell is the most important element in Edwards’ theology. Therefore, the author uses qualitative methods, especially literature review. The author will explore primary and secondary sources to see if Edwards’ concept of hell is the most critical element in Edwards' theology. As a result of this discussion, the writer will show that the concept of hell is not the most critical element in Edwards’ theology because Edwards also has the concept of the glory of God, the sovereignty of God, the love of God, and heaven and the majesty of Christ. The author hopes that this article will clear up the misunderstanding of Edwards. Abstrak: Khotbah Jonathan Edwards, dengan tema Sinners in the Hands of an Angry Godmendapat respons negatif dari pada sarjana. Mereka mengatakan bahwa khotbah Edwards merupakan khotbah yang sadis dan menakutkan, mereka juga menganggap bahwa neraka merupakan elemen paling utama dalam teologi Edwards.Penulis mengunakan metodeliteratur dalam penelitian ini dengan cara menelusuri sumber-sumber primer dan sekunder untuk melihat apakah benar bahwakonsep neraka merupakan elemen paling utama dalam teologi Edwards. Hasil dari pembahasan ini, penulis akan memperlihatkan bahwa konsep neraka bukan elemen paling utama dalam teologi Edwards, karena Edwards juga mempunyai konsep tentang kemuliaan Allah, kedaulatan Allah, kasih Allah,surga dan keagungan Kristus. Penulis berharap tulisan ini akan meluruskan kesalahpahaman terhadap Edwards.